Modelling of liquid heating subject to simultaneous microwave and ultrasound irradiation - Lee, G.L.; Law, M.C.; Lee, V.C.-C. (Applied thermal engineering, 2019)
•Water heating under simultaneous MW and US irradiation was modelled.•Simultaneous MW and US irradiation improves heat uniformity in water.•Hotspots are located in the upper region of water and near the horn tip.•Heat uniformity in water is insensitive to heating time. In this work, a new model that describes liquid heating under simultaneous Microwave (MW) and Ultrasound (US) irradiation was developed in COMSOL Multiphysics and validated against experimental data. This model was used to investigate heat transfer phenomena in water under simultaneous irradiation of MW and US, and compared it with that under individual MW irradiation. The simulation results showed that under simultaneous irradiation, the heat uniformity in the water is greatly enhanced compared to that under individual MW irradiation. Besides, the results indicated that hotspots are mainly located in the upper region of the water sample and in the vicinity of the US horn tip. In addition, the simulation results revealed that the local US power absorption in water is much greater compared to the local MW power absorption, which may cause local overheating. It was also discovered that the heat uniformity in the water sample essentially does not deteriorate with heating time during simultaneous irradiation, which is in contrast to that during individual MW irradiation. The new model could be useful to in the design, optimization and scale-up of combined MW and US systems.